2023
DOI: 10.1039/d3ma00126a
|View full text |Cite
|
Sign up to set email alerts
|

Coconut-husk derived graphene for supercapacitor applications: comparative analysis of polymer gel and aqueous electrolytes

Abstract: Herein, we propose the synthesis of reduced graphene oxide (rGO) using coconut husk as a green and natural resource for supercapacitor (SCs) applications. The electrochemical performance of graphene sheets is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since the activated carbon material at high temperatures possesses a high surface area, high porosity, and optimal amount of oxygen functional groups, it can be a potential candidate for a supercapacitor electrode material. 6,24,32,34,50,51 3.2. Electrochemical Analysis of Activated Carbon.…”
Section: Structural and Morphological Analysis Of Activated Carbonmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the activated carbon material at high temperatures possesses a high surface area, high porosity, and optimal amount of oxygen functional groups, it can be a potential candidate for a supercapacitor electrode material. 6,24,32,34,50,51 3.2. Electrochemical Analysis of Activated Carbon.…”
Section: Structural and Morphological Analysis Of Activated Carbonmentioning
confidence: 99%
“…Considering the energy scarcity issue, activated carbon derived from coconut husk when used for supercapacitor electrodes caught worldwide attention and has the potential to serve as a future green energy storage solution. Until now, only a few studies have been done on supercapacitor electrodes based on coconut-husk-derived activated carbon. Previously, Taer et al utilized activated carbon from coconut husk waste by using a combination of physical and chemical activation processes as a supercapacitor electrode. Their study reported a specific capacitance of 184 F g –1 at a scan rate of 5 mV s –1 for an activation temperature of 900 °C .…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical performance was carried out in 1 M H 2 SO 4 and poly(vinyl alcohol)− KI−H 2 SO 4 polymer gel electrolytes, with the specific capacitance of 500 F g −1 at 1 mV s −1 and specific energy of 36.11 Wh kg −1 . 19 Bhat et al derived activated carbon from the leaves and stems of the cilantro plant using KOH as the activating agent, designing an electrode for use in supercapacitors and a cartridge for water filtration. In a 6 M KOH solution, the electrode demonstrated a specific capacitance of 162.4 F g −1 at a current density of 1 A g −1 in 6 M KOH solution.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Because of their rich availability and sustainability, these biomass-derived materials have become a research hotspot widely used in different applications, like catalysts, electrodes, and absorbents. Tatrari et al synthesized reduced graphene oxide for supercapacitor applications using the coconut husk biomass source. The electrochemical performance was carried out in 1 M H 2 SO 4 and poly­(vinyl alcohol)–KI–H 2 SO 4 polymer gel electrolytes, with the specific capacitance of 500 F g –1 at 1 mV s –1 and specific energy of 36.11 Wh kg –1 . Bhat et al derived activated carbon from the leaves and stems of the cilantro plant using KOH as the activating agent, designing an electrode for use in supercapacitors and a cartridge for water filtration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their rapid charge and discharge rates, long cycle life, and almost no self‐discharge, EDLCs are preferred in applications where fast charging and high power density are crucial such as electric cars and other large‐scale energy storage devices 9,10 . On the other hand, EDLCs might not be a suitable choice for applications where a longer discharge process and high energy density are required 11,12 . The energy density of EDLCs is a subject of intense debate and research.…”
Section: Introductionmentioning
confidence: 99%